Efficacy and safety of pemetrexed plus cisplatin as first-line chemotherapy in advanced malignant peritoneal mesothelioma. (9th July 2019) - Nagata, Yusuke; Sawada, Ryoichi; Takashima, Atsuo; Shoji, Hirokazu; Honma, Yoshitaka; Iwasa, Satoru; Amano, Katsushi; Kato, Ken; Hamaguchi, Tetsuya; Shimada, Yasuhiro; Saruta, Masayuki; Boku, Narikazu
Abstract: Background: Malignant peritoneal mesothelioma (MPeM) is a rare cancer for which no standard systemic chemotherapy has been established. While cisplatin plus pemetrexed, the standard treatment for malignant pleural mesothelioma (MPlM), is usually used for MPeM, its efficacy remains unclear. Methods: We retrospectively reviewed the medical charts of MPeM patients who had received cisplatin plus pemetrexed as first-line chemotherapy between January 2001 and July 2016 at the National Cancer Center Hospital. Patients received cisplatin 75 mg/m 2 and pemetrexed 500 mg/m 2 on day1, repeated every 3 weeks until progressive disease, unacceptable toxicities or patient's refusal to continue. Results: A total of 29 MPeM patients received cisplatin plus pemetrexed. Median progression-free survival and overall survival were 7.1 months (95% CI: 4.8–9.3) and 15.4 months (95% CI: 9.5–21.2), respectively. Among 16 patients with measurable lesions, the response rate was 38%. Incidences of grade 3/4 leukopenia, neutropenia, anemia and thrombocytopenia were 21%, 17%, 14% and 3%, respectively. Non-hematological toxicities were mild, and there were no treatment-related deaths. Conclusions: Cisplatin plus pemetrexed, showing consistent efficacy with MPlM, can be recommended as first-line treatment for unresectable MPeM patients. Abstract : This study evaluated cisplatin and pemetrexed as first-line chemotherapy for unresectable malignant peritoneal mesothelioma, and indicated promising results of the efficacy and safety.